초등학생 대상 영어사교육 유발 요인에 관한 연구 - 오준일(Oh, Junil) (영어교육연구, 2011)
In an effort to explore potential determinants of private English coaching for elementary school students, the study analyzed part of Nam’s data (2011) using different scoring methods and statistical analyses. Survey responses from 672 parents offering private English coaching for their children were tallied and analyzed to examine the extent of private coaching and its potential determinants. Statistical analyses produced several important findings. First, private coaching was found to be prevalent and extensive. Second, parents tended to resort to private coaching, mostly because they wanted their children to have a good command of English. Third, many parents regarded level-differentiated education and satisfactory school instruction as conditions for stopping private coaching. Finally, parents’ socio-economic status, satisfaction with the educational environment in private-coaching institutions, perceived effects of private coaching, and parents’ hopes for their children’s improved English proficiency were found to contribute to the extent of private coaching. Implications of the findings are discussed, and future directions for further research are suggested. KCI Citation Count: 19